New Approach in Religious Studies with Special Reference to Muhammad Abid al-Jabiri - Nirwan Syafrin (Universitas Darussalam Gontor, 2014)
Beginning from the nineteenth century, Arab-Muslim intelligentsias marched to reform their societies. Many things since then have been carried out. They put forward various proposals, advanced numerous ideas and concepts and established several institutions. Nevertheless, their condition has yet improved. In some context, it even deteriorates. Triggered by this situation, a number of Arab and Muslim scholars then embark on a new reform project. But at this time, their reform attempt is materialized in the form of intellectual and cultural project. For they believe that the basic problem and crisis beset their society lies in their understanding of turâts. Thus, unless this understanding is corrected, no genuine reform would be able to be materialized. Muhammad ‘Abid al-Jabiri, a Moroccan scholar, is one of the many Arab scholars who have taken this course. For this purpose, he constructed his own project which he names Naqd al-‘Aql al-‘Arabi. This article specifically attempts to shed light on conceptual apparatus and methods that he uses which this study finds to have originated from different schools of thought of western philosophy and social sciences, important of which is Marxism and postmodernism.